Umpolung Reactions of α‐Imino Esters: Useful Methods for the Preparation of α‐Amino Acid Frameworks. Issue 2 (2nd February 2016) - Mizota, Isao; Shimizu, Makoto
Abstract: This paper summarizes our recent efforts toward the development of tandem reactions utilizing umpolung reactions of α‐imino esters. A highly diastereoselective tandem N‐alkylation–Mannich reaction of α‐imino esters was developed. A tandem N‐alkylation–addition reaction of α‐imino esters derived from ethyl glyoxylate with various aldehydes proceeded to give 1, 2‐amino alcohols. The same reaction also proceeded efficiently using a novel flow system comprising two connected microreactors. Novel syntheses of α‐quaternary alkynyl amino esters and allenoates were developed through the use of umpolung N‐addition to β, γ‐alkynyl α‐imino esters, followed by regioselective acylation. In addition, a highly regioselective tandem N‐alkylation–vinylogous aldol reaction of β, γ‐alkenyl α‐imino esters was discovered. N‐Alkylation of α‐iminophosphonates followed by a Horner–Wadsworth–Emmons reaction with aldehydes occurred to afford enamines, which can be used in a four‐component coupling reaction with methyl vinyl ketone. α‐ N ‐Acyloxyimino esters served as highly efficient substrates for the N, N, C‐trialkylation reaction to introduce various nucleophiles at the imino nitrogen and carbon atoms. Abstract : Our recent efforts toward the development of tandem reactions utilizing umpolung reactions of α‐imino esters are summarized. Various efficient methods such as diastereoselective Mannich reactions, application to flow systems, regioselective syntheses of alkynyl amino esters and allenyl esters, vinylogous aldol reactions, four‐component coupling reactions, N, N, C‐trialkylations, and enamine syntheses are described.